Identification and validation of HaGNA gene as potential RNAi target for management of Old-World bollworm Helicoverpa armigera (Hübner) - A. Boopathi Kumar; Vivek Shah; Joy Das; Rakesh Kumar; K. V. Anu; Pooja Verma; Neelakanth Hiremani; Shivaji Thube; Rahul M. Phuke; G. T. Behere; V. N. Waghmare (Molecular Biology Reports, 2026)

p38 MAPK and MDT-15 mediate SKN-1-dependent metformin-induced protection against mitis group streptococci in Caenorhabditis elegans - Ali Al Hatem; Boopathi Balasubramaniam; Alissa Villhauer; Ali K. Naji; Ransome van der Hoeven (GeroScience, 2026)
Mitis group streptococci are opportunistic pathogens residing in the oral cavity, where they produce hydrogen peroxide (H 2 O 2 ), a key virulence factor contributing to their pathogenesis. We previously demonstrated that these bacteria kill the nematode Caenorhabditis elegans through H 2 O 2 production. Metformin, a widely used biguanide drug for managing blood glucose levels, has shown promising effects on aging by extending lifespan in worms and mice, and has also demonstrated potential cancer treatment. Additionally, pretreatment with metformin enhances the survival of worms and triggers an immune response via the p38 MAPK pathway against various pathogenic bacteria. Based on these observations, we investigated metformin's potential as a therapeutic agent against mitis group streptococcal infections and its underlying mechanisms in the current study. Pretreatment of worms with metformin provided significant dose-dependent protection from streptococcal-derived H 2 O 2 . This protective effect was attributed to the activation of the oxidative stress response transcription factor SKN-1/NRF2. Further analysis revealed that the p38 MAPK pathway and the transcription mediator complex protein MDT-15 are essential for the activation of SKN-1 by metformin. Interestingly, SKN-1 activity, mediated by MDT-15, was found to be independent of the p38 MAPK pathway. Our findings establish that metformin-mediated protection against mitis group streptococcal infections relies on the coordinated action of SKN-1, the p38 MAPK pathway, and MDT-15. These insights suggest that metformin could be a valuable therapeutic agent in combating these infections. Future research should focus on further elucidating the molecular mechanisms involved and exploring the potential clinical applications of metformin in treating these bacterial infections.

Emergence of tomato chlorosis virus in southern India: a new threat to tomato cultivation - B. S. Bharath; Gandhi Karthikeyan; Nagendran Krishnan; N. Boopathi; K. Sivagnanapazham (Indian Phytopathology, 2026)

Thermal and host-plant modulation of development, reproduction, and population growth of the spiraling whitefly, Aleurodicus dispersus (Hemiptera: Aleyrodidae) - T. Boopathi; N. Anusha; J.G. Prasuna; K. Divya (Journal of Asia-Pacific Entomology, 2026)

Genetic dissection of photoperiod response in Indian proso millet (Panicum miliaceum L.) mutants via BLUP modeling of photothermal indices - Ayushi Kumar; Iyanar Krishnamoorthy; Manikanda Boopathi Narayanan; Senthil Alagarswamy; K. Chandrakumar; Mehanathan Muthamilarasan; Ravikesavan Rajasekaran (Journal of Plant Biochemistry and Biotechnology, 2026)

Ecological dynamics and biodegradation potential of freshwater epiplastic microalgae: A sustainable solution for plastic waste management - Sagaya John Paul Joseph; Jayashree K; Sathish Kumar Boopathi; Antony Prakash Rejoy P; Poornima S; Nagaraj Subramani (Journal of Water Process Engineering, 2025)

Floral volatile composition of Jasminum sambac variants developed through colchicine - Vishnupandi S; Ganga M; Rajamani K; Manonmani S; Shobhana V G; Manikanda Boopathi N (Natural Product Research, 2025)

Mushroom - derived antimicrobials – a source of eco-friendly antimicrobial compounds against phytopathogens - S. Dharani; G. Thiribhuvanamala; K. Angappan; N. Swarnakumari; D. Jeya Sundara Sharmila; N. Manikanda Boopathi (Journal of Plant Pathology, 2025)

Correction: Identification of resistance sources for sesame phyllody under epiphytotic conditions in India - M. Santha Lakshmi Prasad; M. Surya Prakash Reddy; P. Duraimurugan; K. Prasindhu; J. Jawaharlal; K. T. Ramya; H. H. Kumaraswamy; M. Sujatha; K. Alivelu; K. Sakthivel; T. Boopathi (Genetic Resources and Crop Evolution, 2025)

Identification of resistance sources for sesame phyllody under epiphytotic conditions in India - M. Santha Lakshmi Prasad; M. Surya Prakash Reddy; P. Duraimurugan; K. Prasindhu; J. Jawaharlal; K.T. Ramya; H.H. Kumaraswamy; M. Sujatha; K. Alivelu; K. Sakthivel; T. Boopathi (Genetic Resources and Crop Evolution, 2025)

Indole-3-acetic acid exposure leads to cardiovascular inflammation and fibrosis in chronic kidney disease rat model - S.P. Ramya Ranjan Nayak; Seenivasan Boopathi; Munisamy Chandrasekar; Siva Prasad Panda; K. Manikandan; Vellapandian Chitra; Bader O. Almutairi; Selvaraj Arokiyaraj; Ajay Guru; Jesu Arockiaraj (Food and Chemical Toxicology, 2024)

Colchicine-induced Jasminum sambac polyploids possessed altered metabolic profile with unique antifungal compounds - S. Vishnupandi; M. Ganga; K. Rajamani; R. Kannan; S. Manonmani; Suhail Ashraf; V. G. Shobhana; N. Manikanda Boopathi (Genetic Resources and Crop Evolution, 2024)

Synthetic azo-dye, Tartrazine induces neurodevelopmental toxicity via mitochondria-mediated apoptosis in zebrafish embryos - B. Haridevamuthu; Raghul Murugan; Boopathi Seenivasan; Ramu Meenatchi; Raman Pachaiappan; Bader O. Almutairi; Selvaraj Arokiyaraj; Kathiravan M. K; Jesu Arockiaraj (Journal of Hazardous Materials, 2024)

Description of a new species in the genus Sarcothelia Verrill, 1928 (Alcyonacea: Xeniidae) from reefs of Gulf of Mannar, South-eastern India - Mahalakshmi Boopathi; Angelo Poliseno; Alvaro Altuna; J. K. Patterson Edward (Marine Biodiversity, 2023)

Wind characteristics of Tamil Nadu coast towards development of microgrid - A case study for simulation of small scale hybrid wind and solar energy system - J. Bastin; A. Haribhaskaran; K. Boopathi; B. Krishnan; R. Vinod Kumar; D.M. Reddy Prasad (Ocean Engineering, 2023)

The impacts of climate change and post bleaching effects on the octocoral communities of Gulf of Mannar, India - Mahalakshmi Boopathi; P Dinesh Kumar; J K Patterson Edward (Journal of Earth System Science, 2021)

Integrated management of soft rot of ginger in Northeastern hills of India - A. Ratankumar Singh; S. K. Dutta; T. Boopathi; S. B. Singh; Lungmuana; Saurav Saha; Vishambhar Dayal; P. Anita; L. Sanajoaba Singh (Indian Phytopathology, 2018)

Diversity in Bird’s Eye Chilli (Capsicum frutescens L.) Landraces of North-East India in Terms of Antioxidant Activities - S. K. Dutta; S. B. Singh; S. Saha; R. S. Akoijam; T. Boopathi; Amrita Banerjee; Lungmuana; Vanlalhmangaiha; Somnath Roy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Identification of mungbean lines with tolerance or resistance to yellow mosaic in fields in India where different begomovirus species and different Bemisia tabaci cryptic species predominate - R. M. Nair; M. Götz; S. Winter; R. R. Giri; V. N. Boddepalli; A. Sirari; T. S. Bains; G. K. Taggar; H. K. Dikshit; M. Aski; M. Boopathi; D. Swain; et al. (European Journal of Plant Pathology, 2017)

Surface Plasmon Resonance Biosensor for Detection of Bacillus anthracis, the Causative Agent of Anthrax from Soil Samples Targeting Protective Antigen - N. Ghosh; G. Gupta; M. Boopathi; V. Pal; A. K. Singh; N. Gopalan; A. K. Goel (Indian Journal of Microbiology, 2013)